Control strategy of wind energy conversion system based on H‐MMC under asymmetrical grid faults. Issue 12 (16th September 2019) - Rong, Fei; Yan, Jiajun; Sun, Wenlong; Huang, Sheng; Wu, Qiuwei
Abstract : This study proposes a topology of wind energy conversion system based on hexagonal modular multilevel converter (H‐MMC), which can connect the wind turbine and the AC grid with one stage conversion. It has the advantages of low power losses, low ripple of capacitor voltage and transformer‐less grid connection. The operation principle of the proposed topology is analysed in detail. Then, the positive and negative sequence control method is proposed to eliminate the second harmonics in the output power of H‐MMC under asymmetrical grid faults. The double proportional resonant (PR) controller is proposed to track arm current references without steady error. The effectiveness of the proposed topology and its control method are verified by simulations and hardware in loop tests.